DAYA TERIMA NUGGET IKAN KEMBUNG DENGAN PENAMBAHAN TEPUNG KACANG TANAH SEBAGAI ALTERNATIF MAKANAN TAMBAHAN BALITA WEIGHT FALTERING - Rosyanne Kushargina; Yang Alifianissa Fath (JOURNAL HEALTH AND NUTRITIONS, 2026)
Toddlers in Indonesia are vulnerable to malnutrition, including being underweight. Underweight is characterized by a weight-for-age of -3 SD to <-2 SD. Underweight toddlers who experience weight loss over the past 3 months experience weight faltering disorders. Weight faltering can be overcome by providing alternative, additional foods with local food-based animal protein content, such as mackerel and peanuts. The objective of study was to evaluate and analyze the acceptability of mackerel nugget products and peanut flour as alternative additional foods for weight-faltering toddlers. The experimental research design used a Completely Randomized Design (CRD) with different concentrations of peanut flour and wheat flour. There were 3 formulas tested in the study (F1 = 15:85, F2 = 20:80, and F3 25:75). The variables studied included hedonic quality, hedonic, nutritional content, omega-3 fatty acids, acceptability, and determination of serving sizes. The acceptability test was conducted on toddlers at PAUD Mentari Sabilillah, Banten. The data obtained were analyzed using the Kruskal-Wallis test and the Mann-Whitney U test. Results of study revealed that the selected formula (F2) has 308.05 kcal of energy, 14.49 g of protein, 18.51 g of total fat, 20.41 g of carbohydrates, and 76.9 mg of omega-3 fatty acids. The acceptability of nuggets in toddlers was 100% with a serving size of 100 grams. The conclusion that mackerel fish nuggets with the addition of peanut flour (20:80) can be used as an alternative supplementary food for weight-fathering toddlers because it is a source of protein and omega-3. For further development, the use of wheat flour can be replaced with other types of flour.Balita di Indonesia rentan mengalami malnutrisi salah satunya adalah underweight. Underweight ditandai dengan berat badan terhadap umur - 3 SD sampai dengan <- 2 SD. Balita underweight yang mengalami penurunan berat badan selama 3 bulan terakhir mengalami gangguan weight falthering. Weight falthering dapat diatasi dengan pemberian alternatif makanan tambahan dengan kandungan protein hewani berbasis pangan lokal, seperti ikan kembung dan kacang tanah. Tujuan penelitian untuk mengevaluasi dan menganalisis daya terima produk nugget ikan kembung dan tepung kacang tanah sebagai alternatif makanan tambahan untuk balita weight faltering. Desain penelitian eksperimental menggunakan Rancangan Acak Lengkap (RAL) dengan perlakuan perbedaan konsentrasi tepung kacang tanah dan tepung terigu. Terdapat 3 formula yang diujikan pada penelitian ini (F1 = 15:85 , F2 = 20:80 dan F3 25:75). Variabel yang diteliti meliputi mutu hedonik, hedonik, kandungan gizi, asam lemak omega 3, daya terima dan penentuan  takaran saji. Uji daya terima dilakukan pada balita di PAUD Mentari Sabilillah, Banten. Data yang didapatkan dianalisis menggunakan uji Kruskal Wallis dan uji lanjutan Mann Whitney. Hasil penelitian menunjukkan pada formula terpilih (F2) memiliki energi 308,05 kcal, protein 14,49 g, lemak total 18,51 g, karbohidrat 20,41 g, dan 76,9 mg asam lemak omega 3.  Daya terima nugget pada balita adalah 100% dengan takaran saji yaitu 100 gram. Kesimpulan penelitian menunjukkan bahwa nugget ikan kembung dengan penambahan tepung kacang tanah (20:80) dapat dijadikan sebagai alternatif makanan tambahan untuk balita weight fathering karena merupakan sumber protein dan omega 3. Pengembangan selanjutnya penggunaan tepung terigu dapat diganti dengan jenis tepung yang lain.